Genetic impairment of folate metabolism regulates cortical interneurons and social behavior - Sadigurschi, Noa; Scrift, Gilad; Hirrlinger, Johannes; Golan, Hava M. (Frontiers in Neuroscience, 2023)
Introduction The implications of folate deficiency in neuropsychiatric disorders were demonstrated in numerous studies. Genetic deficiency in a key folate metabolism enzyme, MTHFR, is an example of the interaction between genetic and environmental risk factors: the maternal MTHFR deficiency governs in-utero nutrient availability, and the embryo’s Mthfr genotype influences its ability to metabolize folates. Here, we explore how the maternal and offspring Mthfr genotypes affect cortical interneuron densities and distributions, mouse social outcome, and the relation of the different interneuron patterns to cortical excitability. Methods Two experiments were conducted to examine the effects of maternal and offspring Mthfr-KO heterozygosity. Mice were tested for direct social interactions (DSIs), repetitive behavior and cortical laminar distribution of interneuron populations expressing glutamate-decarboxylase-65, parvalbumin and somatostatin. Susceptibility to seizure was tested by exposure to pentylenetetrazole (PTZ). Results Maternal Mthfr+/− genotype was associated with suppressed social activities and reduced interneuron densities in all layers of the retrosplenial cortex (RSC). Somatostatin density and the somatostatin/parvalbumin ratio in the RSC and frontal cortex positively correlated with social behavior in the mice. An interaction between maternal and offspring Mthfr genotypes resulted in higher susceptibility of wild-type offspring to PTZ induced seizure. Discussion Maternal folate metabolism was shown to be critical to interneuron ontogenesis. Our results demonstrate that interneurons have a specific susceptibility to folate deficiency that may mediate folate’s involvement in neuropsychiatric disease. The relations between cortical somatostatin interneuron patterns and social behavior highlight this subpopulation of interneurons as a target for further research.